Immunofluorescent Imaging of Kisspeptin in Some Brain Regions in Different Stages of Sexual Cycles of Female Mice - Doğru, Meryem Sedef; Ercan, Zubeyde; Bulmus, Ozgur; Canpolat, Sinan (My University, 2024)
Objective: The aim of the study was to determine kisspeptin intensity by immunofluorescence method in hypothalamus arcuate nucleus (ARC), paraventricular nucleus (PVN), dorsomedial nucleus (DMN) and ventromedial nucleus (VMN) in the diestrus, proestrus and estrus phases of the sexual stages of female mice. Material and Method: In the study, 40 female Balb/c mice aged 5-6 months with an average weight of 35-40 grams were used. All female mice were cycled by vaginal smear with an average of 3 oestrus cycles. Total of 21 animals with regular cycles were selected and divided into 3 groups accord- ing to estrus phases (diestrus, proestrus, estrus and groups, n =7). Animals were decapitated without administering any anesthetic and then brain tissues were frozen on dry ice. Sections were taken from the brain tissue and fluorescent staining steps were applied. At the end of the study, kisspep- tin density in ARC, PVN, DMN and VMN nuclei of the hypothalamus was calculated by immunofluorescence method. Results: It was found that the intensity of kisspeptin higher significantly in the oestrus group compared to the diestrus group in ARC, DMN and VMN. When the intensity of kisspeptin in the PVN was statistically evaluated, insignificant difference was found among the groups. In the DMN and VMN regions, when the estrus and proestrus groups were compared to the diestrus group, the intensity of kisspeptin higher significantly. Conclusion: It was determined that kisspeptin intensity was different in hypothalamic ARC, DMN, VMN and PVN regions at estrous, diestrus and proestrus stages of female mice.
Keywords: Hypothalamus; Kisspeptin; Immunofluorescent; Sexual Cycles.